Pengaruh Metode I’rab Al-Qur’an Terhadap Kemampuan Menghafal Al-Qur’an Santri Pondok Pesantren Nurul Furqon Rembang - Emi Rahmawati; Indra Dwi Jayanti; Amanatul Khomisah (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2022)
I'rab Al-Qur'an is a method of memorizing Al-Qur'an by knowing the meaning of each verse of the Qur'an. The objectives of the study were to find out the I'rab Al-Qur'an method at the Nurul Furqon Islamic Boarding School and its implementation, and to identify the effect of the I'rab Al-Qur'an method on the ability to memorize the Qur'an of the adolescent students of this Islamic boarding school. The method used is a mixed approach, with the type of research being a hypothesis testing study. Data collection techniques using interview techniques, questionnaires, documentation, and observation. Data analysis techniques, namely descriptive analysis and hypotheses. To determine the level of influence of the I'rab Al-Qur'an method on the ability to memorize the Al-Qur'an, Cronbach's Alpha test was carried out using the SPSS 20 program. The results showed that (1) The application of the I'rab Al-Qur'an method in Pondok The Nurul Furqon Islamic Boarding School is running well, focusing on understanding the basic concepts of I'rab first, then applying it in the Qur'an and the teaching system applied, namely the existence of public and private classes; (2) this method has a positive and significant effect on the ability to memorize the Qur'an of students, so that the hypothesis is accepted. The results of the R square test show that the R square value is 55.8%. This shows that by using the regression model, it was found that the independent variable, namely the I'rab Al-Qur'an method, had an effect on the dependent variable, namely the ability to memorize the Qur'an by 55.8%.